1,3-Bis{[(4-methylphenyl)sulfonyl]-oxy}propan-2-yl 4-methylbenzene-sulfonate - Ariffin, Azhar; Tiekink, E.R.T.; Yusof, Y.A.; Ng, S.W.; Abu Hassan, H. (International Union of Crystallography, 2012)
In the title sulfonate derivative,C 24H 26O 9S 3, all atoms apart from those of one of the 4-methyl-benzene-sulfonate residues lie approximately in a disc; the dihedral angles between the approximately orthogonal benzene ring and those in the plane are 74.53 (9) and 67.79 (11)°. In the crystal, molecules are consolidated into the three-dimensional architecture by C - H⋯O interactions. One of the 4-methyl-benzene-sulfonate residues is disordered over two almost parallel positions; the major component refined to a site-occupancy factor of 0.918 (2).